Pengembangan Sistem Informasi Administrasi Kepegawaian Undiksha Berbasis Web - Sastra Kurniawan, I Gede; Made Windu Antara Kesiman, Made; Mahendra Darmawiguna, I Gede (Universitas Pendidikan Ganesha, 2013)
Employee is an important element inorganization due to its role in determining the future oforganization. In organizations, there are specialized departmentsto deal with staff-related issues which is called Human resourcedepartment.. The duty of HRD is to manage or regulateemployment activities and record staff-related data in theorganization. A well operating organization can be distinguishedby its well managed employee administration. And the use oftechnology can improve employee administration system. With theuse of technology, effectiveness of various aspects in managingadministrative information which are indicated by the speed,accuracy, processing time, and correctness of information(validity), can be improved. Implementation of this research wasdeveloped based on waterfall methods and using php asprogramming language with mysql as its database. This softwarehas the ability to record personal information and biography oflecturers and employees in Undiksha. Moreover, this software alsocapable of handling Decreetal information of certain comiteeincluding its related person in charges. this software can also beused to create data regarding credit score for lecturers’ promotion.This software is expected to assist the performance of employeesand lecturers in organizing activities within Ganesha University ofEducation.